Street theatre as propaganda: mass performances and spectacles in Petrograd in 1920. Issue 3 (1st September 2016) - Murray, Natalia
Abstract: The 1917 Bolshevik Revolution aimed to destroy the old imperial state and to build a new homogeneous socialist society. When the Bolsheviks came to power in October 1917, their party contained no more than 350, 000 people in a country of 140 million. Turned overnight into the ruling party, the Bolsheviks aimed to use the power of mass propaganda in order to establish their founding mythology and disseminate their ideas to an overwhelmingly rural and illiterate population. A reason why culture was of such constant concern to the Bolsheviks was because since October Revolution the sphere of culture and ideology was also the sphere of legitimisation of the state. By 1920 culture in all its forms was seen not just as a tool of informing or persuasion of the new society, but now also of its control. The spectacles and mass performances of 1919–1920 constituted the new mythology of the Bolshevik Revolution. Instead of presenting a vision of the future, they provided trusting viewers and participants with an improved version of the Bolshevik past and present – they carried them into Utopia, and showed them the mythical path to it. At the time of economic shortages and starvation, they gave people hope and faith in a bright, Bolshevik, future.